Relation between infarct size and ventricular arrhythmia. - Roberts, R (1975)
In order to determine whether ventricular arrhythmia is quantitatively related to infarct size estimated enzymatically we studied 31 patients with acute myocardial infarction without cargiogenic shock. Infarct size index was estimated from hourly serum creatine kinase (CK) changes during periods of 48 to 72 hours. Ventricular arrhythmia was quantified by automated analysis of continuous electrocardiographic recordings over a period of 20 hours with the use of the Argus/H computer system. Patients were classified into three groups according to infarct size index. Patients in all groups had similar average heart rate, blood pressure, serum potassium, and arterial pH and PCO2 values during the first 10 hours after admission. The total number of ventricular ectopic beats (VEB), frequency of couplets, and ventricular tachycardia, and peak rate of ventricular ectopic beats during the first 10 hours after admission were all related to infarct size index. For example, patients with small, medium, and large estimated infarct size averaged 26, 104, and 405 ventricular ectopic beats, respectively. These results suggest that the severity of ventricular arrhythmia early after myocardial infarction is related to the extent of myocardial injury as estimated enzymatically. Thus the apparent efficacy and therefore the evaluation of antiarrhythmic agents early after myocardial infarction may be influenced by the magnitude of injury sustained by the heart.